Silver‐Mediated N‐Trifluoromethylation of Amides and Peptides. Issue 9 (23rd May 2020) - Zhang, Zhenzhen; He, Jiayan; Zhu, Lin; Xiao, Haiwen; Fang, Yewen; Li, Chaozhong
Summary of main observation and conclusion: We report herein the direct N ‐trifluoromethylation of N ‐H amides. Promoted by AgOTf and 2‐fluoropyridine, the reaction of a variety of amides with Selectfluor, TMSCF3 and CsF proceeds smoothly at room temperature leading to the corresponding N ‐trifluoromethylated products in satisfactory yields. The protocol is also applicable to amino acid derivatives, resulting in efficient and chemoselective N ‐trifluoromethylation of di‐ and tri‐peptides with retention of configuration. A mechanism involving reductive elimination of Ag(III) intermediates to form N—CF3 bonds is proposed. Abstract : Direct and chemoselective N ‐trifluoromethylation of amides and peptides was achieved under mild conditions with retention of configuration.